Traumatic Pseudoaneurysm of Cavernous Internal Carotid Artery following Trans-nasal Endoscopic Decompression of the Optic Nerve - Singh, Manmohan; Mahapatra, AK (Indian Journal of Neurotrauma, 2004)
Traumatic intracranial pseudoaneurysms constitute less than 1% of all intracranial aneurysms. We describe a young patient of head injury, who developed traumatic pseudo aneurysms of cavernous internal carotid artery (ICA) following trans nasal decompression of optic canal for optic nerve compression. Trapping of aneurysm following failed balloon embolization treated the patient successfully.
Keywords: head injury; endoscopic decompression; internal carotid artery; optic nerve injury; traumatic pseudoaneurysm